Penguatan Nilai-Nilai Karakter Nasionalisme Remaja Melalui Tokoh Bajak Laut Topi Jerami dalam Anime One Piece - Muhammad Iqbal; Syamsuri Syamsuri; Thomy Sastra Atmaja; Bistari Bistari; Shilmy Purnama (Mathematics Education Study Program, 2025)
This research aims to provide an overview of the values of youth nationalist character through the straw hat pirate character in the One Piece anime series. The research method used is a qualitative method with a phenomenological approach. The data sources for this research are the head of the Pontianak one piece anime community, members of the Pontianak one piece anime community, and teenagers who love one piece anime aged 15-21 years. Data collection techniques use observation, interviews and documentation. Data analysis techniques for data reduction, data presentation and drawing conclusions. The results of this research show that the nationalist character contained in the main character of the One Piece anime series is unity and oneness, solidarity, independence and willingness to sacrifice. The description of the nationalistic character that teenagers emulate after watching the One Piece anime series is unity and oneness in the activities they carry out, solidarity in terms of friendship, independence shown by strong determination and desire, and willingness to make sacrifices that are applied to everyday life. There are positive impacts such as being able to provide encouragement for personal and social development, being able to form a better character with the surrounding environment, while the negative impact is that they tend to spend more time watching cellphone screens, teenagers are more consumptive by buying knick-knacks or clothes that match the animated characters. One piece, after watching the one piece anime series.